2023
DOI: 10.1097/ta.0000000000003923
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of multiple organ failure in adult polytrauma patients: A systematic review and meta-analysis

Abstract: BACKGROUND Postinjury multiple organ failure (MOF) is the leading cause of late death in trauma patients. Although MOF was first described 50 years ago, its definition, epidemiology, and change in incidence over time are poorly understood. We aimed to describe the incidence of MOF in the context of different MOF definitions, study inclusion criteria, and its change over time. METHODS Cochrane Library, EMBASE, MEDLINE, PubMed, and Web of Science database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 117 publications
0
1
0
Order By: Relevance
“…Postinjury multiple organ failure (MOF) is the leading cause of late death in trauma patients 1,2 . Although MOF was first described half a century ago, a recent systematic review identified no improvements in its incidence over the last 30 years 3 The majority of risk factors and predictors of MOF, such as ISS ≥25, high base deficit, high lactate, high initial creatinine, a low platelet count, and age >65 years are patient‐related or injury‐related, and are therefore not modifiable 2,4,5 . Operations as secondary inflammatory insults (“second hits”) were proposed as risk factors for MOF long ago, and have been frequently discussed in review articles and expert opinions without quality data on their frequency or possible time relationship with MOF 4,6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Postinjury multiple organ failure (MOF) is the leading cause of late death in trauma patients 1,2 . Although MOF was first described half a century ago, a recent systematic review identified no improvements in its incidence over the last 30 years 3 The majority of risk factors and predictors of MOF, such as ISS ≥25, high base deficit, high lactate, high initial creatinine, a low platelet count, and age >65 years are patient‐related or injury‐related, and are therefore not modifiable 2,4,5 . Operations as secondary inflammatory insults (“second hits”) were proposed as risk factors for MOF long ago, and have been frequently discussed in review articles and expert opinions without quality data on their frequency or possible time relationship with MOF 4,6,7 …”
Section: Introductionmentioning
confidence: 99%